Produktivitas Dan Pendapatan Usaha Ternak Babi Rakyat Pasca Pandemi African Swine Fever (Asf) Di Kecamatan Ile Ape Kabupaten Lembata: Productivity And Income Of Smallholder Pig Farming After The Pandemic African Swine Fever (Asf) In Ile Ape Sub-District, Lembata Regency - Maria Milleniti Sura; Maria Krova; Solvi M. Makandolu (Universitas Nusa Cendana, 2023)
A study has been conducted with the aim of determining the productivity of pig farming business after the ASF pandemic, the income level of farmers and the feasibility of pig farming business after the ASF pandemic. This research has been carried out in February 2023. The population in this study is all pig farmers in Ile Ape District, Lembata Regency. Sampling is carried out in stages. The first stage is the determination of six sample villages purposively, the second stage is the determination of random non-proportional sample breeders as many as 20 people from each village. The data analysis methods used are descriptive analysis, revenue analysis, and financial feasibility analysis using Revenue Cost Ratio (R/C) criteria. The results of the study obtained were that the productivity of pigs in Ile Ape District was good with values: litter size of 7.26 average birth weight of 1.49 kg, average weaning weight of 1.83 kg, mortality of weaning cattle of 8.38%, mortality based on age; adult pigs = 1.49%, young pigs of 3.17% and mortality in pigs of 10.34%. The average level of total income obtained by farmers from pig farming is Rp25,053,064/year. The results of the financial analysis showed an R/C value of 1.82. Based on the results of the analysis, it is known that the pig farming business in Ile Ape District, Lembata Regency is profitable and financially viable after the ASF pandemic. Suatu penelitian telah dilakukan dengan tujuan mengetahui produktivitas usaha ternak babi pasca pandemi ASF, tingkat pendapatan peternak, dan kelayakan usaha ternak babi pasca pandemi ASF. Populasi dalam penelitian ini adalah semua peternak babi di Kecamatan Ile Ape Kabupaten Lembata. Pengambilan contoh dilakukan secara bertahap. Tahap pertama penentuan enam desa contoh secara purposive, tahap kedua penentuan peternak contoh secara acak non proporsional sebanyak 20 orang dari setiap desa. Metode analisis data yang digunakan adalah analisis deskriptif, analisis pendapatan, dan analisis kelayakan finansial dengan menggunakan kriteria Revenue Cost Ratio (R/C). Hasil penelitian yang diperoleh adalah produktivitas ternak babi di Kecamatan Ile Ape tergolong baik dengan nilai: litter size sebesar 7,26 rata-rata bobot lahir sebesar 1,49 kg, rata-rata bobot sapih sebesar 1,49 kg, mortalitas ternak prasapih sebesar 8,38%, mortalitas berdasarkan umur; babi dewasa sebesar 1,96%, babi muda sebesar 3,17%, dan mortalitas pada ternak babi sebesar 10,34%. Rata-rata tingkat pendapatan total yang diperoleh peternak dari usaha ternak babi adalah Rp25.053.064/tahun. Hasil analisis finansial menunjukkan nilai R/C sebesar 1,85. Berdasarkan hasil analisis diketahui bahwa usaha ternak babi di Kecamatan Ile Ape Kabupaten Lembata menguntungkan dan layak secara finansial setelah pandemi ASF.